2014
DOI: 10.14195/1647-8606_57-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom assessment: Portuguese adaptation of the Self-Assessed Wisdom Scale – SAWS – by Jeffrey Webster

Abstract: A sabedoria é concebida como a "arte existencial", uma forma de ser que se revela não tanto na exposição teórica, mas sobretudo na capacidade de conduzir a vida da melhor forma. A incidência experimental, relativa ao estudo da sabedoria, intensificou-se nos últimos anos, dado o interesse declarado dos psicólogos cognitivistas e desenvolvimentistas pelos aspetos positivos do desenvolvimento humano.Neste estudo, apresenta-se a versão para a população portuguesa da Self-Assessed Wisdom Scale - SAWS de Jeffrey Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…First, the shortened version of SAWS can help resolve disputes related to the complicated factor structure and dimensionality of the full version of SAWS. The original scale developer and the subsequent validation studies have generally failed to fully replicate the five latent factor structure of the 40 item scale [2,18,23,33,34]. For example, a recent study showed that some SAWS items did not load on any factor and that the openness dimension had a questionable Cronbach's alpha of 0.68 [18,43,80].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the shortened version of SAWS can help resolve disputes related to the complicated factor structure and dimensionality of the full version of SAWS. The original scale developer and the subsequent validation studies have generally failed to fully replicate the five latent factor structure of the 40 item scale [2,18,23,33,34]. For example, a recent study showed that some SAWS items did not load on any factor and that the openness dimension had a questionable Cronbach's alpha of 0.68 [18,43,80].…”
Section: Discussionmentioning
confidence: 99%
“…1 This study also provides empirical evidence to support the factor structure of the BSAWS using CFA. Numerous SAWS related studies have used only EFA to evaluate the factorial validity of the scale, without verifying the construct validity with CFA [2,18,33]. The only SAWS validation study to use CFA was based on five sub-scales, which served as the latent factors for estimating the loadings on the wisdom construct rather than evaluating all 40 items.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations